Optimization of microwave Assisted Process for Extraction of Nutmeg Seed Essential Oil - SAFEENA P.A SRAVAN RAJ SREELATHA E STENY SIMON THEERTHA M.S; Dr. Prince M.V (Guide) (Tavanur 2017 Department of Food & Agricultural Process Engineering)
Optimization of microwave Assisted Process for Extraction of Nutmeg Seed Essential Oil
Optimization of microwave Assisted Process for Extraction of Nutmeg Seed Essential Oil